2015
DOI: 10.1002/pros.22952
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of GAS5 lncRNA levels and mTOR inhibitor action in prostate cancer cells

Abstract: BACKGROUND New therapies are required for castrate‐resistant prostate cancer (CRPC), and growth‐arrest specific 5 (GAS5) lncRNA, which riborepresses androgen receptor action, may offer novel opportunities in this regard. This lncRNA promotes the apoptosis of prostate cancer cells and its levels decline as prostate cancer cells acquire castrate‐resistance, so that enhancing GAS5 expression may improve the effectiveness of chemotherapies. Since GAS5 is a member of the 5' terminal oligopyrimidine gene family, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 39 publications
4
77
0
Order By: Relevance
“…GAS5 was initially identified during screening for potential tumor suppressor genes (29) and is a stress-inducible gene, which is differentially expressed in healthy and tumor tissues/cell lines (30). In addition, GAS5 has been demonstrated to be involved in the regulation of the cell cycle (31) and to function as a tumor suppressor in human T cells, and breast and prostate cancer cell lines by inducing apoptosis (10,11,32,33). Furthermore, reduced expression of GAS5 and/or its snoRNAs has been observed in head and neck squamous cell carcinomas, and gastric and cervical cancer (34)(35)(36), indicating that it serves an important role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 was initially identified during screening for potential tumor suppressor genes (29) and is a stress-inducible gene, which is differentially expressed in healthy and tumor tissues/cell lines (30). In addition, GAS5 has been demonstrated to be involved in the regulation of the cell cycle (31) and to function as a tumor suppressor in human T cells, and breast and prostate cancer cell lines by inducing apoptosis (10,11,32,33). Furthermore, reduced expression of GAS5 and/or its snoRNAs has been observed in head and neck squamous cell carcinomas, and gastric and cervical cancer (34)(35)(36), indicating that it serves an important role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences demonstrated that lncRNA growth arrest-specific 5 (GAS5) acted as a powerful regulator of various biological activities, including tumor metastasis [29], vascular remodeling [30], autoimmune and inflammatory diseases [31]. Recently, GAS5 has been reported to involve in autophagy in NSCLC cells [32], and negatively correlated with mTOR [33,34], which is a crucial regulator of autophagy [35]. Although GAS5 has been suggested to mediate autophagy program, the underlying mechanism still remains to be further confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore a therapeutic target for gastric cancer and has been proposed as a potential biomarker for poor prognosis (19). GAS5 has also been shown to promote the apoptosis of prostate cancer cells, and decreased expression of GAS5 may lower the effectiveness of chemotherapeutic drugs in prostate cancer patients (20,21). GAS5 expression is both essential and sufficient for normal growth arrest in T cell lines and human peripheral blood T cells (22).…”
mentioning
confidence: 99%